Molecular detection of Epstein–Barr virus in invasive ductal carcinoma of the breast: a case–control study: EBV in invasive ductal breast carcinoma - Mohammed Mahmoud, Mahmoud; Abdulla Kamil Abdulla; Dler Omar Mohammed (Cellular and Molecular Biology, 2025)
The uncertain contribution of Epstein–Barr virus (EBV) to the etiological processes underlying invasive ductal carcinoma (IDC) of the mammary gland, especially in relation to its molecular interactions within inflamed histological contexts, remains to be elucidated. This case–control research assessed the link between EBV infection and mammary IDC in a population of Iraqi females from Kirkuk. A total of 300 breast tissue specimens preserved in paraffin blocks were evaluated, including 150 samples diagnosed with IDC and 150 samples classified as fibroadenoma serving as controls. EBV latent membrane protein-1 expression was identified through the application of immunohistochemical staining and polymerase chain reaction methodologies. EBV positivity, defined as detection by both IHC and PCR, was observed in 7.3% of IDC cases and 4% of controls, with no statistically significant difference between groups (P=0.996). No significant association was found between EBV presence and estrogen or progesterone receptor status, while Her-2 expression differed significantly between EBV-positive and EBV-negative patients (P<0.001). EBV was more frequently detected in grade I tumors and stage II breast cancers, and older patients showed a higher prevalence of EBV infection. The results indicate that although Epstein–Barr virus (EBV) is identifiable in a fraction of invasive ductal carcinoma (IDC) breast specimens, a definitive causative relationship between EBV presence and IDC occurrence within this demographic is not established. Nonetheless, EBV detection appears to exhibit higher frequency in specific histopathological grades, clinical stages, and patient age categories.